William Moorcroft, Potter Individuality by Design - Mallinson, Jonathan (Open Book Publishers, 2023)
William Moorcroft (1872-1945) was one of the most celebrated potters of the early twentieth century. His career extended from the Arts and Crafts movement of the late Victorian age to the Austerity aesthetics of the Second World War. Rejecting mass production and patronised by Royalty, Moorcroft's work was a synthesis of studio and factory, art and industry. He considered it his vocation to create an everyday art, both functional and decorative, affordable by more than a privileged few: 'If only the people in the world would concentrate upon making all things beautiful, and if all people concentrated on developing the arts of Peace, what a world it might be,' he wrote in a letter to his daughter in 1930. 'William Moorcroft, Potter: Individuality by Design' is a pioneering study by Jonathan Mallinson, Emeritus Fellow of Trinity College, Oxford. It follows the career of William Moorcroft through a wealth of private papers, letters and diaries, business correspondence and published reviews in newspapers, trade magazines and art journals. Richly illustrated with examples of his pottery, it explores what lay behind the unique impact of work sought by museums and treasured in homes the world over. The book examines an artist's very individual response to the turbulent half century in which he worked. It will appeal to both specialists and general readers with an interest in pottery, the decorative arts, and the cultural history of the times.